Adolescents' cognitive capacity reaches adult levels prior to their psychosocial maturity: Evidence for a "maturity gap" in a multinational, cross-sectional sample - Grace Icenogle (2019)
© 2019 American Psychological Association. All countries distinguish between minors and adults for various legal purposes. Recent U.S. Supreme Court cases concerning the legal status of juveniles have consulted psychological science to decide where to draw these boundaries. However, little is known about the robustness of the relevant research, because it has been conducted largely in the U.S. and other Western countries. To the extent that lawmakers look to research to guide their decisions, it is important to know how generalizable the scientific conclusions are. The present study examines 2 psychological phenomena relevant to legal questions about adolescent maturity: cognitive capacity, which undergirds logical thinking, and psychosocial maturity, which comprises individuals' ability to restrain themselves in the face of emotional, exciting, or risky stimuli. Age patterns of these constructs were assessed in 5,227 individuals (50.7% female), ages 10-30 (M = 17.05, SD = 5.91) from 11 countries. Importantly, whereas cognitive capacity reached adult levels around age 16, psychosocial maturity reached adult levels beyond age 18, creating a "maturity gap" between cognitive and psychosocial development. Juveniles may be capable of deliberative decision making by age 16, but even young adults may demonstrate "immature" decision making in arousing situations. We argue it is therefore reasonable to have different age boundaries for different legal purposes: 1 for matters in which cognitive capacity predominates, and a later 1 for matters in which psychosocial maturity plays a substantial role.